UNCOVERING GREEN FLAG CONCEPT OF ATLAS CORRIGAN IN IT STARTS WITH US - Sri Rahmadani Basri; Sukardi Weda; Muh Safar Nur (Faculty of Languages and Literature, Universitas Negeri Makassar, 2026)
The concept of green flag in romantic relationships has gained increasing attention as a representation of healthy and supportive partner. However, its application in literary studies, particularly in relation to masculinity remains underexplored. This study aims to analyze the representation of the green flag concept in relationships through the character of Atlas Corrigan in the novel It Starts With Us by Colleen Hoover. It also highlights how Atlas’s actions and behaviors reflect green flag traits and demonstrate a form of non-hegemonic masculinity within a contemporary social context. This study adopts a sociological approach in literature, which sees literary works as a reflection of social realities, cultural values, and norms of interaction that exist in society. The theoretical framework applied includes the concept of the green flag in relationships, Judith Butler's (1990) theory of Gender Performativity, as well as research on masculinity. This research method uses a descriptive qualitative approach with data sourced from dialogues, narratives, and character interactions of Atlas Corrigan that are relevant to the focus of the research. Data were collected using a close reading technique and analyzed using thematic coding based on the green flag indicators, gender performativity, and masculinity type. The findings show that atlas consistently demonstrates green flag traits such as empathy, healthy communication, respect for boundaries, and emotional support. These repeated behaviors construct a non-hegemonic masculinity that is more egalitarian and supportive, reflecting a shift in contemporary social values toward healthier romantic relationship and more inclusive masculine identities in popular literature. This study contributes to literary studies by offering a new perspective on positive masculinity and encouraging the inclusion of healthy relationship representations in literary works.